2021
DOI: 10.5267/j.msl.2021.1.021
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of panic buying behavior during the COVID-19 pandemic

Abstract: The new Coronavirus disease (COVID-19) pandemic triggers panic buying behavior among consumers in several countries. Previous research on panic buying behavior is less likely to look at the phenomenon from the perspective of consumers (demand-side). Therefore, this study aims to examine the influence of media credibility and social contagion on panic buying behavior and the mediating effect of consumer anxiety in the relationship between media credibility, social contagion and panic buying behavior. Data was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Individual motivation to adopt or not adopt consumption coping is explained by the TMI. Previous studies have demonstrated that people use both approach consumption coping, such as cutting costs, panic buying and increased health expenditures (Putri et al, 2021), and avoidance Consumption coping to deal with pandemic stress consumption coping, such as compulsive and impulsive buying (Liu and Black, 2011;Seale et al, 2009;Sneath et al, 2009;Sneath et al, 2014), during collective tragedies such as floods, pandemics and earthquakes. Therefore, this study proposes that people with high pandemic-induced stress will try more approach and avoidance consumption coping.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Individual motivation to adopt or not adopt consumption coping is explained by the TMI. Previous studies have demonstrated that people use both approach consumption coping, such as cutting costs, panic buying and increased health expenditures (Putri et al, 2021), and avoidance Consumption coping to deal with pandemic stress consumption coping, such as compulsive and impulsive buying (Liu and Black, 2011;Seale et al, 2009;Sneath et al, 2009;Sneath et al, 2014), during collective tragedies such as floods, pandemics and earthquakes. Therefore, this study proposes that people with high pandemic-induced stress will try more approach and avoidance consumption coping.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…However, the pandemic also induced wasteful consumption intentions in certain product categories of essential items such as food and toilet paper [32][33][34][35][36]. Millennials also engaged in panic buying to cope with the stress of not having access to these essential items amid the pandemic [39]. While there was an increase in the consumption of food and toilet paper among millennials, apparel shopping decreased during this time [39].…”
Section: Commitment To the Environment As A Mediator Between Covid-19...mentioning
confidence: 99%
“…While sustainable consumption is conceptually less wasteful in nature, increased instances of both sustainable consumption and wasteful consumption amid the pandemic seem contradictory. Although some studies suggested that the consumption of toilet paper, groceries, and food increased among millennials amid the pandemic [39], intentions for purchasing leisure items and apparel decreased during this time [39]. Therefore, it could be implied that the increase or decrease in purchase intentions amid the pandemic was largely dependent on the product category.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change in buying behaviour is not unexpected as they tended to serve as coping strategies for life in isolation. This level of panic buying is not unrelated to mainstream news impending scarcity and supply chain disruptions with three keywords immediately coming to mind on the situation: fear, panic, risk (Arafat et al, 2020;Putri et al, 2021). These keywords underpin the kind of buying situation ongoing globally, characterising consumer buying decision making and instigating purchase of whatever consumers can lay their hands on.…”
Section: Introductionmentioning
confidence: 99%